Contribución del 2% y la recaudación del impuesto a la renta en Ecuador durante el periodo 2019-2021 - Cáceres Chico, Erick Fabricio (2024)
SUMMARY The objective of this research work is to analyze and compare the income tax collection amounts in Ecuador for the years 2020 and 2021, taking the year 2019 as a reference. It is also intended to compare the collection of the microenterprise regime with the contribution of the general regime. In order to determine if there is a significant difference with the implementation of said tax tool, the methodology used in the research is bibliographic documentary with a quantitative approach of a comparative nature where the panel data technique was used with the help of the matrix of double entry based on the information of the data provided by the Internal Revenue Service of Ecuador, therefore the 24 provinces of the country are used as the study population, which allows analyzing the collection amounts at the annual, monthly and regional level as well as the monthly analysis of the collection of each of the income tax taxes such as monthly withholdings, the advance payment of income tax, income tax for both natural and legal persons, income tax for inheritances legacies and donations, both for the year 2019 and 2020 where 2021 is characterized by the implementation of the Microenterprise regime, this comparison reveals that Ecuador presents a decrease in the years 2020 and 2021 compared to the year 2019 and based on the monthly variation, It can be seen that the most affected months are between April and December. In turn, the statistical program IBM SPSS version 29 was used to perform the Shapiro-Wilk normality test, where, since the data does not follow a normal distribution, the statistics were used. non-parametric with the Wilcoxon test, the results show that at the level of annual income tax collection there are no significant variations in the years 2020 and 2021, so it is concluded that although there is a decrease in income tax collection income, the 2% contribution does not significantly affect the collection of the General Regime. Keywords: Income tax, Monthly withholdings, income tax advance, natural persons, legal entities, inheritances, legacies and donations, Microenterprises.